2022
DOI: 10.1371/journal.pone.0271574
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes medications and associations with Covid-19 outcomes in the N3C database: A national retrospective cohort study

Abstract: Background While vaccination is the most important way to combat the SARS-CoV-2 pandemic, there may still be a need for early outpatient treatment that is safe, inexpensive, and currently widely available in parts of the world that do not have access to the vaccine. There are in-silico, in-vitro, and in-tissue data suggesting that metformin inhibits the viral life cycle, as well as observational data suggesting that metformin use before infection with SARS-CoV2 is associated with less severe COVID-19. Previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…This study showed that metformin use in diabetics was associated with less severe COVID-19 compared with sulfonylurea use but not dipeptidyl-peptidase-4-inhibitors, two other common diabetes medications ( Bramante et al, 2022a ). More specifically, metformin use was associated with a lower risk of ventilation and mortality ( Bramante et al, 2022a ). Further studies also determined that diabetic metformin users who were hospitalized with COVID-19 had a shortened hospital stay duration, a lower rate of intubation, and decreased inflammatory markers compared to diabetics on other oral hypoglycemic medications ( Usman et al, 2022 ).…”
Section: Clinical Trials With Metformin During Acute Sars-cov-2 or In...mentioning
confidence: 75%
See 2 more Smart Citations
“…This study showed that metformin use in diabetics was associated with less severe COVID-19 compared with sulfonylurea use but not dipeptidyl-peptidase-4-inhibitors, two other common diabetes medications ( Bramante et al, 2022a ). More specifically, metformin use was associated with a lower risk of ventilation and mortality ( Bramante et al, 2022a ). Further studies also determined that diabetic metformin users who were hospitalized with COVID-19 had a shortened hospital stay duration, a lower rate of intubation, and decreased inflammatory markers compared to diabetics on other oral hypoglycemic medications ( Usman et al, 2022 ).…”
Section: Clinical Trials With Metformin During Acute Sars-cov-2 or In...mentioning
confidence: 75%
“…One study determined that metformin use was beneficial in preventing severe COVID-19 outcomes in subjects with prediabetes or polycystic ovary syndrome (PCOS, a condition that is commonly treated with metformin off-label) compared to control-matched participants ( Chan et al, 2022 ). Another retrospective study evaluated the associations between metformin use and COVID-19 outcomes in diabetics compared to diabetics on other therapeutically equivalent diabetes monotherapies ( Bramante et al, 2022a ). This study showed that metformin use in diabetics was associated with less severe COVID-19 compared with sulfonylurea use but not dipeptidyl-peptidase-4-inhibitors, two other common diabetes medications ( Bramante et al, 2022a ).…”
Section: Clinical Trials With Metformin During Acute Sars-cov-2 or In...mentioning
confidence: 99%
See 1 more Smart Citation
“…Confounders were identified based on clinical assessment of variables associated with the exposures and the outcomes and follows selections used in previous comparisons of these antidiabetic drug classes. 24 Comorbidities and medications of interest were identified from patient records in the previous 12 months using ICD-10 codes and medication lists and were defined using translated OMOP concepts.…”
Section: Methodsmentioning
confidence: 99%
“… 25 , 26 Several observational analyses in patients with T2DM describe an association between prevalent metformin use and less severe COVID-19 compared to prevalent use of other therapeutic equivalents for T2DM. 24 , 27 However, few observational analyses have assessed PASC as an outcome when comparing metformin use at the time of SARS-CoV-2 infection in adults with T2DM.…”
Section: Introductionmentioning
confidence: 99%